2022
DOI: 10.1021/acsomega.1c06148
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Potential and Chemical Profiling of Euphorbia abyssinica Endowed with Docking Studies

Abstract: Chemical profiling of both fruit and aerial part extracts of Euphorbia abyssinica via ultra-performance liquid chromatography−mass spectrometry (UPLC-MS) showed them to be a rich source of diverse compounds. A total of 39 compounds in both extracts including flavonoids and phenolic compounds were identified as predominant metabolites. The antioxidant activity of both extracts was evaluated using three different in vitro assays (DPPH, ABTS, and FRAP assays). The E. abyssinica fruit extract demonstrated more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Thirty-nine compounds including flavonoids and phenolic compounds as main metabolites were identified in both extracts. 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-nine compounds including flavonoids and phenolic compounds as main metabolites were identified in both extracts. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Thirty-nine compounds including flavonoids and phenolic compounds as main metabolites were identified in both extracts. 11 Euphorbia plant latexes were considered toxic substances because they could cause irritation of mucous membranes in humans, especially the nose and mouth. 12 However, several previous studies revealed the cytotoxic activity of Euphorbia plants.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous dietary antioxidants, such as vitamin E, carotenoids, ascorbic acid, and polyphenols, also exhibit oxidative stress-protective pathways. , Currently, using a combination of herbs to build a treatment that lowers oxidative stress is possible, , and various herbal substances have various antioxidant benefits . Therefore, the natural antioxidants derived from food or plant sources and byproducts of food processing are getting a lot of attention today. Cancer is a deadly disease triggered by mutated genes, environmental influences, and disrupted cell-regulatory proteins. The incidence of cancer has been increasing in current decades and is one of the major health concerns of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Therefore, the natural antioxidants derived from food or plant sources and byproducts of food processing are getting a lot of attention today. 12 14 Cancer is a deadly disease triggered by mutated genes, environmental influences, and disrupted cell-regulatory proteins. The incidence of cancer has been increasing in current decades and is one of the major health concerns of the 21st century.…”
Section: Introductionmentioning
confidence: 99%